Democratization of the school space: Management, in-service training and permanence of students - Risso, Divine Lozetti; Carvalho, Naiara Hernandes; Falsarella, Ana Maria (Seven Editora, 2023)
This text deals with educational management from the democratic perspective, its influence on the in-service training of the school team and the prevention of dropout, and its contribution to the permanence of students in the institution. It highlights the relevance of professional post-graduation in encouraging researchers to carry out research linked to their means of work. It aims to present theoretical studies on democratic-participatory management and leadership developed as a result of two professional master’s works within the line of research in Educational Management. The first work deals with teacher training in the implementation of a new pedagogical model in early childhood education. The second explores the permanence of students in technical education and the prevention of dropout. Both have democratic management as a point of convergence. A bibliographic exploration of legal and theoretical-conceptual frameworks carried out through narrative review was the methodology used. The main authors consulted: Demo, Lück, Martins, and Paro. It was concluded that, when it is intended to improve the pedagogical and relational spheres of the school, patterns of shared leadership are essential. DOI:https://doi.org/10.56238/alookdevelopv1-106